Entre grades e macas : costurando encontros e afetos com as pessoas em cumprimento de medida de segurança na Unidade de Custódia e Tratamento Psiquiátrico do Espírito Santo - Lopes, Priscila Simenc Rocha (2018)
"Fools" as well as "criminals" are historically considered to be a potential risk to society and therefore are excluded by it. But what about "crazy criminals"? The literature indicates that this part of the population has been suffering for years with the lack of assistance in their basic rights, placed in asylum or even in common prisons without at least the opportunity of an appropriate treatment for their state of health. What determines the course of these lives? Who are these people, what are their characteristics, their stories? These inquiries have motivated us to develop the present research that aims to understand which aspects of the life of people with mental disorder who have committed crimes and are in compliance with Security Measure at the Hospital of Custody of the ES, today called Unit of Custody. Our focus on the cartographic ethos and the research as an event allowed us to look at data from the charts and meetings with people living in the institution in order to perceive the power games and the strategies of power that guide our perception about this population and also, lead their lives to silencing and domination. The attentive reading of some of Foucault's works, such as "Watch and Punish" and "Infamous of History" followed us along the way and led us to a critical look at the process of constructing the notion of madman as dangerous individual, unworthy of speech and existence in the social space. The madman who gains visibility after the clash with power, who takes this life and determines what will become of it. Favret-Saada, Suely Rolnik and other contemporaries presented us with the possibility of a new look at research, a sensitive and sensorial way. In this way, we have been walking the paths, breaking out and adding new certainties, knowing stories and being affected by them. We took the path of happening, we realized that the stories told / written did not correspond to the complete history of those people, that their existences are not reduced to the crime once practiced and that led them to that institution. We do not conclude, we can not do it, we close this research comprehending that it is necessary to know the human who inhabits the asylum, to know its madness and its history is to break with the paradigm that they are only "madmen and criminals." To know their stories is to bet on the life that pulsates and that can be free, free of pain, death and abandonment.